Quantitative and qualitative assessment of maternal and child health services among hard-to-reach communities in Adamawa state, Nigeria - Mohammed B. Hamman; Adamu M. Tukur; Amitabye L. Ramma (AOSIS, 2023)
Background: Recent global reports highlighted the significance of improving the quality of healthcare delivery in all settings, including rural and Hard-to-reach communities, as a central strategy for attaining sustainable development goals. Objectives: This study aimed at assessing and document relevant data associated with delivering qualitative Maternal and Child health (MCH) services in the hard-to-reach (HTR) communities using carefully selected indicators. Methods: The study used a mixed-design approach of quantitative and qualitative methods. Results: This study report high performance on the first antenatal visit (ANC 1), use of modern contraceptives (CPR), Penta 3, measles vaccination coverage, and, Low dropout rate also noticed in Penta 3, thus signifying a generally good performance in all the local government areas (LGAs). Furthermore, Yola South, Fufore, Toungo, Ganye and Michika LGA were found to be the best performing LGAs on the selected maternal and Child indicators, namely: (ANC1), ANC4, ANC8, Institutional delivery rate, and Contraceptive Prevalence Rate (CPR), while Gombi, Guyuk and Madagali LGAs were the poorest performing LGAs. The poor performance of these LGAswere associated with human and environmental interferences: ongoing insecurity, high HTR communities due to mountains and riverine, high illiteracy, inadequate outreach services, poverty, lack of adequate emergency transport system, inadequate human resource for health (HRH), inadequate and poor infrastructure, many communities lacking primary healthcare center. Conclusion: The assessment highlights the coverage of LGAs with low utilization of MCH services in HTR communities of Adamawa State, the reasons for the low coverage, and the possible strategies for increased utilization of these services. These findings suggest an urgent need for designing efficient outreaches for the delivery of maternal newborn and child's intervention in HTR communities.